The effects of mg addition on the microstructure and mechanical properties of Thixoformed Al-5%Si-Cu alloys - Salleh, Mohd Shukor; Omar, Mohd Zaidi; Syarif, Junaidi (Elsevier, 2014)
In this study, the effects of different amounts of magnesium (Mg) on the microstructures and tensile properties of thixoformed Al–5%Si–Cu alloys were investigated. Three different alloys containing various amounts of Mg (0.5, 0.8 and 1.2 wt%) were prepared through the cooling slope casting technique, before they were thixoformed using a compression press. Several of the thixoformed samples were then treated with a T6 heat treatment, that is, solution treatment at 525 C for 8 h, quenching in warm water at 60 C, followed by aging at 155 C for 4 h. All of the samples were then characterised by optical microscopy (OM), scanning electron microscopy (SEM) energy dispersive X-ray (EDX) spectroscopy and X-ray diffraction (XRD) analysis as well as by tensile tests. The results revealed that magnesium was able to refine the size of a-Al globules and the eutectic silicon in the samples. It was also observed that a compact p-Al9FeMg3Si5 phase was formed when the magnesium content was 0.8 wt% and 1.2 wt%. The mechanical properties of the thixoformed alloys improved significantly after the T6 heat treatment. The highest attainment was recorded by the latter alloy (i.e. with 1.2 wt%Mg) with its ultimate tensile strength (UTS) as high as 306 MPa, yield strength (YS), 264 MPa, and elongation to fracture of 1.8%. The fracture of thixoformed alloy with a low Mg content (0.5 wt%) showed a combination of dimple and cleavage fracture, whereas in the alloy that contained the highest Mg content (1.2 wt%), cleavage fracture was observed.